Knowledge domain and emerging trends in HIV pre-exposure prophylaxis: A visualization analysis via CiteSpace - Chen, Xi; Lai, Yu (Frontiers in Microbiology, 2023)
Background: As an effective strategy that reduces transmission among people at high risk of human immunodeficiency virus (HIV), pre-exposure prophylaxis (PrEP) has revolutionized HIV prevention. This article aims to provide a reference for the development of relevant research and the formulation of prevention and control policies for HIV. Methods: Through CiteSpace software, this study aims to present a comprehensive overview of the HIV PrEP knowledge structure, hotspots, and frontiers. We searched the Web of Science Core Collection for studies published between 2012 and 2022 related to HIV PrEP, and 3243 papers remained after selection. Results: The number of HIV PrEP publications has increased over the past few years. A close integration and exchange of HIV PrEP research findings has taken place between countries and authors. Major ongoing research trends include long-term injection PrEP, the impact of chlamydia on HIV PrEP, and individual awareness of and attitude toward HIV PrEP. Thus, more attention should be paid to innovations and breakthroughs in drugs, the factors that affect HIV transmission and susceptibility, and the future promotion of public acceptance of HIV PrEP. Conclusions: This study offers a systematic, objective and comprehensive analysis of the related articles. It will assist scholars in understanding the dynamic evolution of HIV PrEP research and identifying future research areas to better advance the development of the field.